Synthesis of substituted flavones and chromones using a Wells-Dawson heteropolyacid as catalyst - Bennardi, Daniel Oscar (2008)
In this work, we report the use of bulk and silica-supported Wells-Dawson acid (H2P2W18O62.24H2O) as reusable, heterogeneous catalysts to obtain substituted flavones and chromones for the cyclization of 1-(2-hydroxyphenyl)-3-aryl-1,3-propanediones. The reaction experiments were performed using toluene as solvent at reflux and in the absence of solvent, at 110°C. Under these conditions eleven examples were obtained with very good yields (82-91%) and high selectivity. The catalysts were easily recycled and reused without loss of their catalytic activity. The presented synthetic method is a simple, clean and environmentally friendly alternative for synthesizing substituted flavones and chromones.